The Combined Impact of Female and Male Body Mass Index on Cumulative Pregnancy Outcomes After the First Ovarian Stimulation - Zhao, Zhonghua; Jiang, Xue; Li, Jing; Zhang, Menghui; Liu, Jinhao; Dai, Shanjun; Shi, Hao; Liang, Yuling; Yang, Li; Guo, Yihong (Frontiers in Endocrinology, 2021)
Objectives To evaluate the combined impact of male and female BMI on cumulative pregnancy outcomes after the first ovarian stimulation. Design Retrospective cohort study. Setting University-affiliated reproductive medicine center. Patients A total of 15,972 couples undergoing their first ovarian stimulations from June 2009 to June 2016 were included. During the follow-up period between June 2009 and June 2018, 14,182 couples underwent a complete ART cycle involving fresh embryo transfer and subsequent frozen embryo transfers (FETs) after their first ovarian stimulations. Patients with a BMI <24 kg/m2 served as the reference group. Patients with a BMI ≥ 24 kg/m2 were considered to be overweight, and those with a BMI ≥28 kg/m2 were considered to be obese. Intervention(s) None. Primary Outcome Measure The primary outcome was the cumulative live birth rate (CLBR), which defined as the delivery of at least one live birth in the fresh or in the subsequent FET cycles after the first ovarian stimulation. Results In the analyses of females and males separately, compared with the reference group, overweight and obese females had a reduced CLBR (aOR 0.83, 95% CI 0.7.92 and aOR 0.76, 95% CI 0.64–0.90). Similarly, overweight males had a reduced CLBR (aOR 0.91, 95% CI 0.83–0.99) compared with that of the reference group. In the analyses of couples, those in which the male was in the reference or overweight group and the female was overweight or obese had a significantly lower CLBR than those in which both the male and female had a BMI <24 kg/m2. Conclusions The CLBR is negatively impacted by increased BMI in the female and overweight status in the male, both individually and together.